2017
DOI: 10.1017/sjp.2016.103
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Intervention Program to Improve Employability of University Students

Abstract: In the current socioeconomic situation, the need to improve employability of potential workers is especially relevant. The aim of this study was to evaluate the efficacy of an intervention program focusing on improving employability of university students. To do this, a two-group study was designed: one group undertook the intervention program and the other group were used for comparison. Two measurements were taken at different times (pre-intervention and post-intervention). The sample consisted of 271 univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Hence, the Western employability literature focuses on competences that contribute to graduate employability (Knight and Yorke 2004;Dacre Pool and Sewell 2007;Kumar 2007;Bridgstock 2009;Pegg et al 2012;Cole and Tibby 2013). In this context, studies perceiving employability from a perspective of competence-development are well established (Hennemann and Liefner 2010;Boahin and Hofman 2013;Jackson 2014;Hernández-Fernaud et al 2017). When it comes to defining employability, in this stream of literature three authors are cited the most: Hillage and Pollard (1998), Harvey (2001) and Yorke (2006).…”
Section: A Competence-based Approach To Employability: Definitionmentioning
confidence: 99%
“…Hence, the Western employability literature focuses on competences that contribute to graduate employability (Knight and Yorke 2004;Dacre Pool and Sewell 2007;Kumar 2007;Bridgstock 2009;Pegg et al 2012;Cole and Tibby 2013). In this context, studies perceiving employability from a perspective of competence-development are well established (Hennemann and Liefner 2010;Boahin and Hofman 2013;Jackson 2014;Hernández-Fernaud et al 2017). When it comes to defining employability, in this stream of literature three authors are cited the most: Hillage and Pollard (1998), Harvey (2001) and Yorke (2006).…”
Section: A Competence-based Approach To Employability: Definitionmentioning
confidence: 99%
“…Temple (2012) contends that modern universities need to rise above the traditional teaching and research role to locate their new position at the heart of regional development and regeneration. In approaching this new role, universities need to focus on graduate employability (Álvarez-González et al , 2017; Hernández-Fernaud et al , 2017) and create graduates who can articulate basic skills, including numeracy and literacy. In this context, Mason et al (2009) found that numeracy is one of the greatest graduate employability assets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given such critical findings with important implications, the need for sustained investigations into how greater numerical literacy could be developed by graduates is no longer argued. These findings are echoed byHernández-Fernaud et al (2017) and theLearning and Skills Council -LSC (2006). In the specific area of overconfidence in numeracy skills, very few studies have been conducted.…”
mentioning
confidence: 94%
“…Given such critical findings with far-reaching implications, the need for sustained investigations into how greater numerical literacy could be developed by graduates is clear. This view is echoed by Hernández-Fernaud et al (2017) and the Learning and Skills Council (LSC) (2006). Therefore, there have been calls from educationalists, policymakers, government departments and universities to pay greater attention to generic skills (McLarty, 2005), communication skills (writing and speaking), team working skills (Krassadaki et al, 2014) and numeracy skills (Black and Yasukawa, 2010; Raybould and Sheedy, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Temple (2012) contends that modern universities need to move beyond their traditional roles of teaching and research such that they are located at the heart of regional development and regeneration. In approaching this new role, universities need to focus on graduate employability (Álvarez-González et al, 2017; Hernández-Fernaud et al, 2017) and produce graduates who can articulate basic skills, including numeracy and literacy. From the same perspective, Mason et al (2009) find that numeracy is one of the greatest assets with regard to graduate employability, and that, in the development of such assets, employer involvement in curriculum design is important.…”
Section: Literature Reviewmentioning
confidence: 99%